Correlation of Growth Parameters with Yield of Two Cassava Varieties - Amarullah Amarullah; Didik Indradewa; Prapto Yudono; Bambang Hendro Sunarminto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
The correlation of major growth parameters with the yield of cassava in different growth phases was investigated in 2013 and 2014. This experiment was conducted to assess the effect of two cassava varieties and the different growth phases to the yield and yield components. In experiment, the varieties as treatment were arranged in a randomized complete block design (RCBD) with three replications. Two varieties consisted of superior Adira-4 and local varieties Singgah were used. The growth parameters (plant height, stem diameter, leaf number) and yield components (number of tuber, weight per tuber and tuber yield) in early growth phase, maximum vegetative growth phase and charging tuber phase, were observed. Based on the correlation results, the growth parameters and the yield highly affected to the final outcome of cassava tubers at different growth phases. In the early growth phase, occurs high demand to assimilate with the expense of storage root. However, from the maximum vegetative phase, growth parameters began to show a significant positive contribution to the tuber weight. Weight of fresh tuber in both varieties increased at the charging of tubers phase and thereafter (enlarged bulb). The early growth phase and maximum vegetative phase might not generate a significant contribution to the final yield of cassava tuber. Making those two periods were not suitable time for optimum harvesting result, and it still depended on the variety and its allocation.